Anti-inflammatory effect of Alpinia galanga extract on acute inflammatory cell model of peripheral blood mononuclear cells stimulated with TNF-α - Bambang Cahyono; Meiny Suzery; Nur Dina Amalina (Medicinski glasnik, 2023)
Aim Studies have shown that SARS-Cov-2 has the ability to activate proinflammatory cytokine leading to acute inflammation. During the SARS-Cov-2 infection, an increase of the secretion of production TNF-α in seen in COVID-19 patients along with a decrease in anti-inflammatory cytokine IL-10, and growth factor TGF-β caused cytokine storm and damaged tissues. Alpinia galanga extract contains several secondary metabolites with strong antiinflammation and antioxidant effect. The aim of this study was to evaluate the effect of Alpinia galanga extract on peripheral blood mononuclear cells (PMBC) acute inflammation cells model stimulated with TNF-α. Methods Alpinia galanga was extracted under maceration methods on ethanol 96%. The PMBC was collected from three healthy humans and isolated using ficol reagent and cultured with the TNF-α 100pg/mL for 72 h. The TNF-α levels were evaluated under ELISA reader. Furthermore, the IL-10 and TGF-β gene expression was analysed using qRT-PCR after 24 h treatment with Alpinia galanga extract. Results Alpinia galanga extract has no cytotoxic effect on Vero cells with IC50 value of >1000µg/mL. The PBMC acute inflammation cells model stimulated by TNF-α 100pg/mL, after 72 h induction the PBMC cells significantly expressed a high level of TNF-α up to 341±10.87 pg/mL. Furthermore, the treatment of Alpinia galanga significantly increased the anti-inflammatory cytokine IL-10 and growth factor TGF-β in dose dependent manner. Conclusion These findings suggested that Alpinia galanga extract has strong antiinflammation activity.
Keywords: acute inflammation; Alpinia galanga extract; IL-10; PMBC